The Effect of Easy and Security Perceptions On Interest In Using E-Money On Ovo Users In Somba Opu Sub-District - Gadis Nurul Insani; Haedar Akib; Aris Baharuddin (Public Resource Innovation Management and Excellence, 2024)
This study aims to determine the description and influence of Easy and Security Perceptions either partially or simultaneously On Interest In Using E-Money On OVO Users In Somba Opu Sub-District, Gowa District. The population of the research is OVO users in Somba Opu Sub-District, Gowa District. Determination the sample use is the sample formulated by Slovin with an error rate of ten percent, the number of sample obtained is as many as one hundred respondents. Data collection technique is questionnaires are tested for validity and reliability. The data obtained were processed using data analysis and the help of SPSS version twenty five program which of data normality test, multiple linear regression analysis, t test, F test and coefficient of determination. The results showed that the variables of Easy, Security Perceptions and Interest Using E-money in the good category. Variables of Easy and Security Perceptions had a significant effect partially or simultaneously On Interest In Using E-Money On OVO Users In Somba Opu Sub-District, Gowa District. This is based on the results of the t test and F test on the data obtained.